Makna Spiritualisme dalam Pandangan Etika dan Religi Jawa Melalui Jaranan Sekarmelati di Desa Sumberawan Singosari: Kajian Antropolinguistik - Sari, Lely Kurnia; Zakiyah, Millatuz (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2024)
This research will focus on spiritual meaning through Javanese ethics and religion in jaranan art which has a long history and its own meaning. The researcher believes that this view will be more eye-opening and provide insight that is not widely known to the general public and will direct the Javanese view that is used to center on Javanese ethics or morality and Javanese religion in Kejawen with the art of Kuda Lumping as well as better explain the essence of the existence of Jaranan art so that the meaning is distorted. -meanings that often occur are not repeated and understand how important the meaning of culture is in society. The research method used is a qualitative descriptive research method with an ethnosemiotics approach. This research aims to explore the meaning of spiritualism in the art of Jaranan Sekarmelati in Toyomarto village, Singhasari.